Leadership Training Toolkit for State-Owned Enterprises (SOEs) : Boards and Owners - World Bank; International Finance Corporation (Washington, DC: World Bank, 2022)
The Leadership Training Toolkit for State-Owned Enterprises (‘SOE Leadership Toolkit’) was developed jointly by the World Bank and IFC (World Bank Group) to support countries’ efforts to build capacity of State ownership entities, SOE boards, and SOE senior management. It addresses the growing need for curricula specifically adapted for SOEs, considering the significant role and impact of SOEs on public finances, the economy and delivery of public services.